Interactions of FK506 and Rapamycin With FK506 Binding Protein 12 in Opportunistic Human Fungal Pathogens - Vellanki, Sandeep; Garcia, Alexis E.; Lee, Soo Chan (Frontiers in Molecular Biosciences, 2020)
Over the past few decades advances in modern medicine have resulted in a global increase in the prevalence of fungal infections. Particularly people undergoing organ transplants or cancer treatments with a compromised immune system are at an elevated risk for lethal fungal infections such as invasive candidiasis, aspergillosis, cryptococcosis, etc. The emergence of drug resistance in fungal pathogens poses a serious threat to mankind and it is critical to identify new targets for the development of antifungals. Calcineurin and TOR proteins are conserved across eukaryotes including pathogenic fungi. Two small molecules FK506 and rapamycin bind to FKBP12 immunophilin and the resulting complexes (FK506-FKBP12 and rapamycin-FKBP12) target calcineurin and TOR, respectively in both humans and fungi. However, due to their immunosuppressive nature these drugs in the current form cannot be used as an antifungal. To overcome this, it is important to identify key differences between human and fungal FKBP12, calcineurin, and TOR proteins which will facilitate the development of new small molecules with higher affinity towards fungal components. The current review highlights FK506/rapamycin-FKBP12 interactions with calcineurin/TOR kinase in human and fungi, and development of non-immunosuppressive analogs of FK506, rapamycin, and novel small molecules in inhibition of fungal calcineurin and TOR kinase.